2021
DOI: 10.18502/jad.v15i2.7491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Geographical and Climatic Factors on the Distribution of Phlebotomus papatasi (Diptera: Psychodidae) in Golestan Province, an Endemic Focus of Zoonotic Cutaneous Leishmaniasis in Iran, 2014

Abstract: Background: Phlebotomus papatasi is known as the main vector of zoonotic cutaneous leishmaniasis. This study aimed to investigate the effect of geographical and bioclimatic factors on the Ph. papatasi distribution. Methods: A total of 34 villages were selected, and sampling was performed three times using 120 sticky traps in each selected village. All the collected species were mounted and identified their species. The densities of Ph. papatasi were measured in all the village… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…These findings support that P. papatasi activity occurs during the hot season, where both minimum and maximum temperatures are high, and low temperatures during the Data analysis further supports the hypothesis of an intricate association between climatic factors, vector density, and disease incidence. It reinforces previous reports on the seasonal activity of P. papatasi [48,49] and the impact of precipitation and air temperature as significant factors affecting P. papatasi distribution [40,50,51]. In addition, moisture, wind [52], aridity, or surface climate variables [10] also influence vector activity and dispersal capability.…”
Section: Association Of Zcl Incidence and The Climatic Parameters In ...supporting
confidence: 89%
“…These findings support that P. papatasi activity occurs during the hot season, where both minimum and maximum temperatures are high, and low temperatures during the Data analysis further supports the hypothesis of an intricate association between climatic factors, vector density, and disease incidence. It reinforces previous reports on the seasonal activity of P. papatasi [48,49] and the impact of precipitation and air temperature as significant factors affecting P. papatasi distribution [40,50,51]. In addition, moisture, wind [52], aridity, or surface climate variables [10] also influence vector activity and dispersal capability.…”
Section: Association Of Zcl Incidence and The Climatic Parameters In ...supporting
confidence: 89%
“…According to a study conducted in Morocco, higher relative humidity levels were positively correlated with increased sandflies abundance which is in line with our findings that’s suppose that a range of humidity from 25% to 55% increases enormously the number of CL cases in the Ghardaïa region. 46 Another study conducted in Biskra province in Algeria found out the same correlation coefficient between humidity and CL cases. 47 However, a study in Golestan province, Iran has confirmed that precipitation is the most important factor in the density of CL vectors.…”
Section: Discussionmentioning
confidence: 66%
“…First, a correlation test was performed between two variables based on the Spearman correlation coefficient (Spearman's r). When |r| ≥ 0.7, there is a strong correlation between variables [37][38][39]. Then, we included all bioclimate variables in the model for a prerun.…”
Section: Collection and Processing Of Environmental Variablesmentioning
confidence: 99%